The artistic identity of a cycle “Between the children of nature” by Ahatanhel Krymsky (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2023)
In the article the author finds out the interests of A. Krymsky, who was a writer, a scientist and a polyglot, in the history, culture and everyday life in Turkey. Science activity, general works about the history of Turkey were a basement of a literature and translation activities of A. Krymsky. The cycle “Between the children of nature” from the collection “Palm branches” by A. Krymsky reconstructs the artistic image of Turkey, is a part of ukrainian literature (together with folklore dumas, historical songs, literary works), expands tematic range of ukrainian literature process from the end of the 19th century to the beginning of the 20th century, affirms the general conception of ukrainian literature modernism. The exotic world of Turkey (nature, everyday life and so on), that was applied effectively by the author, the literary appointments of psychologize approximate ukrainian readers to the perception of the culture of the region. In the cycle “Between the children of nature” A. Krymsky submits the image of Turkey in the folklore aspect by translating Ottoman folk songs. The author makes his translation as accurately as possible in lexical, rhythmic and emotional parts. In his translations he reproduces the world of feelings of a lyrical hero (sadness, delays, dreams, addictions, expectations, pain, frustrations). A lyrical hero attempts to sincere mutual love. Using the power of emotions, sensitivity, a lyrical hero of the cycle written by A. Krymsky lines with the modernistic trends of ukrainian and world literature of the beginning of the 20th century. Thus the author complements the system of images that is presented also in works of Ivan Franko, Johann Wolfgang von Goethe, Jan Kasprowicz and others. Combinate total of feelings, emotions of the main hero, lexical, syntactic, narrative aspects of the cycle, rhythm, the semantic content of symbolic images, an emotional part of the texts approximate Ahatanhel Krymsky`s translations to the examples of ukrainian folklore. Then the young man, who is a warrior, takes part in the military campaigns. This fact shows and deepens sincere relationships between both heroes. It also complements the conception of a lyrical hero. It is a final part of the dramatic feelings of the lyrical hero of the cycle.
Keywords: a lyrical hero; a translation; a cycle; a modernism; a folklore; exotic images